A Review of Edible Fruits from the Rosaceae Family: Rich Sources of Phytochemicals with Potent Anti-inflammatory Properties - Saeed Ghasemi; Mahnaz Khanavi; Fatemeh Yousefbeyk* (Research Journal of Pharmacognosy)
Inflammation is one of the main causes of many non-infectious diseases like asthma, diabetes, and rheumatoid arthritis. Various inflammatory mediators and pathways are involved in the inflammation process. Also, overproduction of reactive oxygen species (ROS) under the stimulus of pro-inflammatory cytokines can lead to serious damages. The edible fruits from the Rosaceae family are commonly consumed in daily diets and contain phytochemicals with antioxidant and anti-inflammatory properties. Despite their numerous biological and clinical advantages, the application of Rosaceae fruit extracts in the formulation of pharmaceuticals for managing chronic inflammatory diseases is being neglected. This review will summarize the current state of knowledge on phytochemicals, in vitro, in vivo, and clinical studies of the most popular Rosaceae fruits. It will also highlight the suggested molecular mechanisms of action for their anti-inflammatory properties. The databases, including Web of Science, PubMed, Scopus, and Google Scholar were systematically searched with keywords such as phytochemical, anti-inflammatory, and the scientific name of each fruit. All studies support the antioxidant activity of Rosaceae fruits. In several studies, the inactivation of the NF-κB pathway was identified as the main anti-inflammatory mechanism of action. In many studies in vitro exposure to fruit extracts resulted in reducing the secretion of pro-inflammatory cytokines. Some studies also reported an increase in the secretion of IL-10 and a number of studies revealed the inhibitory effects of fruit extracts on COX-1 and COX-2. In conclusion, the potential of these extracts in formulating functional foods and pharmaceuticals to improve inflammatory conditions should be further explored.